Estudos de validação com a versão portuguesa da Escala de Dificuldades na Regulação Emocional (EDRE) - Veloso, Mário (2011)
The domain of Emotion Regulation is in expansion and its relevance in different therapeutics settings led to the development of several measures to assess this dimension. The Difficulties in Emotion Regulation Scale pretends to assess the difficulties that adult people have when they try to regulate their emotions. The study presented here permitted to adapt one scale for the Portuguese population – Difficulties in Emotion Regulation Scale (Gratz & Roemer, 2004) – which measures individual differences related to difficulties in emotion regulation in a sample of 431 college students. The results show that EDRE has an high internal consistency (Cronbach’s α = ,93), good testretest stability (r=.841) and good external validity with other measures. This scale also can discriminate between clinical and non-clinical samples. The principal components analysis didn’t replicate the original solution and this version has seven components. Despite the existence of some limitations, this scale provides an useful contribution to clinical domain.